PENGEMBANGAN MODEL PEMBELAJARAN DEBAT, ANALISIS DAN TEMUAN (DAT) BERBASIS DIGITAL LIFE SKILL - Apdoludin; Guswita, Reni; Andriani, Diyan; Isma Putri, Dexza (Jurnal Muara Pendidikan, 2024)
Limited learning resources, lack of educators' abilities, low student thinking skills, difficulty in training skills, and analyzing materials are serious problems in this study. This study is a development research or Research and Development (R & D). The purpose of the study was to determine the validity, practicality, and effectiveness of the DAT learning model based on digital life skills that was developed. The population of the study was 124 students of grade IV of Elementary School 106/II Sungai Binjai. The sampling technique used was simple random sampling. The sample in the study was 36 students. The trial was limited to 9 students. Data collection techniques were model validation sheets, observations, questionnaires, and interviews. The reliability test in this study used a Likert scale. The results showed that the reliability of the instrument was 74, with a percentage of 92.5% (good) by learning model design experts. 63 with a percentage of 78.75% (good) by language experts. 76 with a percentage of 95% (good) by material experts and 2880 with a percentage of 89.51% (strongly agree) by students. For further researchers, it is recommended to pay attention to the limitations of the study, so that they can further refine the model that has been developed.